Detection of adulterants and evaluate the quality of selected commercial pickles and chutneys collected from various local markets in Jashore, Bangladesh - Alam, S M Shamiul; Alam, Asraful; Sultana, Razmin; Akhtaruzzaman, Md; Afrin, Maria (Asian Journal of Medical and Biological Research, 2023)
In Bangladesh, pickles and chutneys are very popular appetizers that give main dishes more taste. In this present study quality of selected commercial pickles and chutneys were evaluated by conducting physicochemical parameters and analyzing the adulterant. A total 19 samples were used for this experiment. The pickle and chutney samples were evaluated for physicochemical parameters including moisture content, acidity as citric acid, sodium benzoate, and arsenic in laboratory. The results suggested that, highest concentration of moisture content (49.80±0.21%), acidity (1.85±0.02 mg/Kg) and sodium benzoate (363.30±0.26 mg/Kg) were found in Tamarind chutney (C-1), Jujube chutney (B-3) and Mixed chutney (E-1) respectively. However, all of the samples estimated arsenic (As) levels remained within the corresponding guideline limit. It is concluded that samples of moisture content (57.89%), acidity (68.42%) and sodium benzoate (15.79%) were higher than BSTI standard which is not suitable for food safety. However, pickles and chutneys are available in both good and bad quality in the market. Asian J. Med. Biol. Res. 2023, 9 (1), 9-13